ANALISIS Z-SCORE¬ UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI 2016-2018 - Rustandi, Handry; Suherman, Acep (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the effect of Z-Score on bankruptcy. The variables used in this study are the Altman Z-Score and bankruptcy. This research was conducted using quantitative methods with an associative approach.The population in this study is the financial statements of the 2016-2018 food and beverage sub-sector companies as many as 4 food and beverage companies and 47 samples are taken from the financial statements. in this research the sampling with saturated sampling technique. data collection techniques using secondary data. The analysis technique used is the classic assumption test, multiple linear analysis, and hypothesis testing. The results of this study address: the independent variable Altman Z-Score method while the dependent variable is bankruptcy. The ratio of working capital to the total assets has a positive significant effect. Which addressed the ratio of working capital to total assets significantly influence the ratio of working capital. This refers to the ratio of working capital to Altaman Z-Score.